2021
DOI: 10.3389/fneur.2021.599498
|View full text |Cite
|
Sign up to set email alerts
|

Inside the Thrombus: Association of Hemostatic Parameters With Outcomes in Large Vessel Stroke Patients

Abstract: Background: Actual clinical management of ischemic stroke (IS) is based on restoring cerebral blood flow using tissue plasminogen activator (tPA) and/or endovascular treatment (EVT). Mechanical thrombectomy has permitted the analysis of thrombus structural and cellular classic components. Nevertheless, histological assessment of hemostatic parameters such as thrombin-activatable fibrinolysis inhibitor (TAFI) and matrix metalloproteinase 10 (MMP-10) remains unknown, although their presence could determine throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Moreover, the mechanisms by which the prognostic value of the 24-h PLR after rtPA appears to be greater than that at baseline have not been well established. An increase in platelet count after thrombolytic therapy may be responsible for delayed thrombosis, leading to reocclusion and rethrombosis ( 31 ). A previous study revealed that rtPA potentially induces the elevation of matrix metalloproteinase-9 and chemokine ligand-2, which mediate blood–brain barrier disruption and may lead to hemorrhagic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mechanisms by which the prognostic value of the 24-h PLR after rtPA appears to be greater than that at baseline have not been well established. An increase in platelet count after thrombolytic therapy may be responsible for delayed thrombosis, leading to reocclusion and rethrombosis ( 31 ). A previous study revealed that rtPA potentially induces the elevation of matrix metalloproteinase-9 and chemokine ligand-2, which mediate blood–brain barrier disruption and may lead to hemorrhagic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinase-10 (MMP-10) and TAFI have been shown to colocalize with inflammatory cells and platelets in all thrombi retrieved from large vessel occlusion stroke patients [ 50 ]. Most importantly, subjects who died within 3 months had higher VWF and lower TAFI content in thrombi, suggesting that the histological composition and distribution of different thrombi hemostatic components have prognostic and therapeutic implications [ 50 ]. Two recent reviews have highlighted the impact of thrombus composition and organization on the efficacy of thrombolysis in the setting of acute ischemic stroke (AIS) [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%